Pengaruh Rendam Kaki Dengan Air Hangat Pada Lansia Untuk Menurunkan Tingkat Insomnia Di Wilayah Kelurahan Balecatur - Shinta, Riadinata; Pratiwi, Fika; Husna, Fauzul; Aqila, Fitri (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Aging is a natural process that is accompanied by a decrease in physical condition with a visible decrease in organ function. The aging process makes the elderly more prone to sleep disorders. Handling sleep disorders can be done in two ways, namely pharmacologically and non-pharmacologically. Non- pharmacological management is a safer alternative option, namely by soaking warm water feet. The benefits of warm water are to make the body more relaxed, get rid of muscle aches and stiffness, and lead to better sleep. The purpose of this study was to identify whether there is an effect of warm water foot bath on sleep quality in the elderly in the Balecatur Village Area. The type of research used is quasi experiment which is included in the pre test and post test one group design. Statistical data analysis used is Paired t- test and this research was conducted for 5 consecutive days. The sampling technique in this study was purposive sampling with 30 respondents. This study based on statistical tests obtained P value = 0.001, which means that there is a significant difference before and after warm water foot soak therapy. There is a significant effect of warm water foot soak on sleep quality in the elderly. Researchers hope that the elderly will always do this warm water foot soak as a necessity for themselves to reduce sleep quality problems